Inbreeding pada Populasi Banteng (Bos javanicus d’Alton 1832) di Kebun Binatang Surabaya - Reny Sawitri; Mariana Takandjandji (Buletin Plasma Nutfah, 2012)
Inbreeding Population of Banteng (Bos javanicus d’Alton 1832) at Surabaya Zoo. Reny Sawitry and Mariana Takandjandji. Banteng (Bos javanicus d’Alton 1832) is one of wildlife that is maintained in Surabaya Zoo, their mating system happened from a couples, and so overlap from generation to next generation. The purposed of this research was to determine effective population size, genetic diversity, and the change of physical and physiological of the herd. The methods used in this study were analysis DNA mitochondria from hair samples, description of physical and physiological change, and inbreeding coefficient. The results showed that effective populations size of herd in Surabaya Zoo tended to decline from productive age of banteng. Haplotype diversity of herd population was very low, the distance of genetic intra population zerro, and it’s genetic diversity was very homogen. This occured caused change in sex ratio of which male dominated the offspring population. Subsequently, the impact of inbreeding was the change of physic and physiology of banteng such as skin colour, sterile and infertile. Inbreeding that happened in Surabaya Zoo affected extinction of third population because of individual number of live sex less than one. The inbreeding coeficient was calculate using of pedigree analysis and inbreeding rate per generation based on the population structure. The calculation result of inbreeding coeficient was 0.42, while the inbreeding rate was 4.3% per generation. Finally, it’s needed to supply banteng from nature to fix offsprings and it’s genetic diversity. AbstrakBanteng (Bos javanicus d’Alton 1832) merupakan salah satu satwa liar yang dipelihara di Kebun Binatang Surabaya (KBS). Sistem perkawinan banteng di lokasi ini dimulai dari bibit tunggal dan overlap antar generasi. Tujuan penelitian adalah untuk mengetahui keragaman genetika banteng di KBS melalui analisis DNA mitokondria, deskripsi perubahan fisik dan fisiologi banteng, gambaran nilai koefisien dan laju inbreeding per generasi. Metode yang digunakan adalah penghitungan ukuran populasi efektif, deskripsi perubahan fisik dan fisiologi serta koefisien dan laju inbreeding. Hasil penelitian menunjukkan bahwa ukuran populasi efektif banteng cenderung menurun dilihat dari umur produktif. Diversitas haplotipe populasi banteng di KBS sangat rendah, sehingga jarak genetik dalam populasi = 0 dan dapat dikatakan keragaman genetiknya sangat homogen. Rata-rata nilai koefisien inbreeding adalah 0,42 dan laju inbreeding 4,3% per generasi. Hal ini dapat dilihat dari keturunan jantan daripada betina. Perkawinan secara inbreeding penurunan fisik serta fisiologi banteng di KBS, seperti terjadinya kemandulan dan ketidaksuburan. Inbreeding juga mengakibatkan kepunahan pada populasi yang ada karena pada generasi ketiga jumlah individu tiap kelamin yang hidup kurang dari satu. Dengan demikian diperlukan pasokan banteng dari alam untuk memperbaiki keturunan dan keragaman genetik.